2006
DOI: 10.1002/prot.21057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and tissue‐specific expression of two lepidopteran farnesyl diphosphate synthase homologs: Implications for the biosynthesis of ethyl‐substituted juvenile hormones

Abstract: The sesquiterpenoid juvenile hormone (JH) regulates insect development and reproduction. Most insects produce only one chemical form of JH, but the Lepidoptera produce four derivatives featuring ethyl branches. The biogenesis of these JHs requires the synthesis of ethyl-substituted farnesyl diphosphate (FPP) by FPP synthase (FPPS). To determine if there exist more than one lepidopteran FPPS, and whether one FPPS homolog is better adapted for binding the bulkier ethyl-branched substrates/products, we cloned thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 57 publications
4
74
0
Order By: Relevance
“…DponGPPS/FPPS protein was 99% identical to a putative FPPS from Dendroctonus jeffreyi (13) and shared 75%, 70%, 62%, 62%, 50%, and 49% amino acid identity with the FPPSs from A. grandis (11), I. pini (13), Tribolium castaneum (GenBank accession no. XP_972537), P. cochleariae (12), Choristoneura fumiferana (19), and Drosophila melanogaster (GenBank accession no. CAA08919), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DponGPPS/FPPS protein was 99% identical to a putative FPPS from Dendroctonus jeffreyi (13) and shared 75%, 70%, 62%, 62%, 50%, and 49% amino acid identity with the FPPSs from A. grandis (11), I. pini (13), Tribolium castaneum (GenBank accession no. XP_972537), P. cochleariae (12), Choristoneura fumiferana (19), and Drosophila melanogaster (GenBank accession no. CAA08919), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). In the latter, branching order within each cluster did not perfectly match that of recent family-level lepidopteran phylogenies (e.g., LepTree Team, 2007), particularly for PPO1, but such discrepancies are not uncommon for trees constructed using a single gene (see, for example, Cusson et al, 2006). An earlier PPO/ hemocyanin phylogeny (Terwilliger and Ryan 2006) yielded a similar branching pattern, despite very different taxonomic sampling outside the Lepidoptera.…”
Section: Choristoneura Fumiferana Ppo Polypeptidesmentioning
confidence: 95%
“…Similar N-terminal extensions are found in other insect sequences (Fig. 2, Cusson et al, 2006) and also are observed in plant (Cunillera et al, 1997) and mammalian FPPSs (Martin et al, 2007). The N-terminal extension of AgFPPS displays the characteristics of mitochondrial-targeting peptide and contains RXXS sequence, which is a consensus cleavage motif in mitochondrial targeting peptides (Von Heijne et al, 1989, Fig.…”
Section: Discussionmentioning
confidence: 73%
“…The female boll weevil produces a sesquiterpene pheromone (Hedin et al, 1979), which is presumably synthesized from FPP. FPPS has been sequenced from several insects including, Agrotis ipsilon (Castillo-Gracia and Couillaud, 1999), Bombyx mori (Kikuchi et al, 2001), Drosophila melanogaster (Sen et al, 2007a), and Choristoneura fumiferana (Cusson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%